Co-small Module - Li, Wang; Jin, Cuncheng (Journal of Informatics and Mathematical Sciences, 2015)
The main goal of the present article is to study basic properties of co-small modules. Let $R$ be a Noetherian ring, For all co-small module $B$ and index $I$, we get isomorphic $Torn(B;\prod A_i)\cong \prod Torn(B;A_i)$. Finally, we prove that If two modules of the sequence $0 → A→ B→ C→ 0$ are co-small modules, so is the third.